From Slave Trade to Banking in Nineteenth-Century Spain - y Alharilla, Martín Rodrigo (Comparativ, 2021)
In the nineteenth century, there was a certain chronological parallel between the ever-increasing incorporation of the Spanish into the slave trade and the construction of a modern banking system in Spain. On an individual level we find numerous examples of former captains or slave traders who later converted to respectable bankers as Pedro Martínez Pérez de Terán, José de Abarzuza Imbrechts, Mariano Serra Soler, José María Serra Muñoz, Mariano Flaquer Lluch, Esteban Gatell Roig, Jaime Badia Padrines, Antonio Vinent Vives, Manuel Calvo Aguirre, Antonio López y López, and José Canela Raventós, among others. Through their capital or their activity, all of them contributed to the creation of different financial institutions in nineteenth-century Spain. This article offers a first approach to this phenomenon. I will do so on the basis of three different banks founded in 1844, 1846, and 1876, respectively, in two Spanish port cities (Cádiz and Barcelona) and in whose foundation and development former slave traders played a major role. We will therefore analyse the participation of varous slave traders in the Banco de Cádiz and then repeat the same analysis in two financial entitites with their headquarters in the Catalan capital: the Banco de Barcelona and the Banco Hispano Colonial, respectively.